Nursing home leader response during COVID-19: a qualitative descriptive study about use of external resources during the pandemic - Amy Vogelsmeier; Lori L. Popejoy; Alisha Harvey Johnson; Steven Miller; Lisa Young; Roy A. Thompson; Lona Mody; Marilyn Rantz; David R. Mehr (BMC, 2024)
Abstract Background US nursing homes were ground zero for COVID-19 and nursing home leaders faced multiple challenges to keep residents and staff safe. Understanding the leader's role and their use of external resources to rapidly respond to the pandemic is important to better prepare for the next infectious disease outbreak emergency. The purpose of this study is to describe Missouri nursing home leaders' use of external resources to manage challenges encountered during the pandemic. Methods This qualitative descriptive study uses data from semi-structured interviews conducted with leaders from 24 Midwestern nursing homes between March 2022 and March 2023. Interviews were transcribed verbatim and analyzed using Dedoose software. Directed content analysis, guided by Donabedian's Structure, Process, Outcome framework, was used for analysis. Interviews were conducted as part of a larger mixed-methods study focused on developing knowledge and recommendations to improve US nursing homes' capacity to respond to infectious disease outbreaks. Results Forty-three interviews were conducted across the 24 homes. Participants included administrators (n = 24), nurse leaders (n = 19), and infection preventionists (n = 16). Six sub-categories of external resources/support were used by leaders to manage challenges during the pandemic:1) corporate support and communications, 2) statewide resources, 3) community-based resources, 4) health care coalitions focused on emergency response planning, 5) existing affiliations with local organizations i.e., hospitals, and 6) community members and families. Corporate support was a primary resource; however, it was limited to chain-based homes. Leaders from standalone homes seemed most reliant on statewide agencies, existing affiliations, and other community-based resources due to their lack of corporate connections. Health care coalitions were few, but when available, helped nursing homes prepare for the pandemic onset. Family and community members were vital despite being off-site from nursing homes at the pandemic onset. Conclusion Leaders played a pivotal role in accessing and using external resources to manage challenges during the pandemic. Statewide and community-based agencies and existing affiliations were particularly critical for standalone homes who otherwise had little to no means of support. Federal, state and local agencies must consider opportunities to build multi-agency regional collaborations, local health care coalitions and community-based partnerships that include nursing homes as member. Finally, community members and family were important in providing support, thus closing visitation is a double-edged sword that needs careful, future consideration.